Taxonomic Identity of Gamochaeta americana and Gamochaeta coarctata (Gnaphalieae, Asteraceae) - Freire, Susana E.; Grossi, Mariana A.; Iharlegui, Laura; Abarca, Camila L.; Monti, Claudia; Bayón, Néstor D. (Phytotaxa, 2021)
Gamochaeta (Asteraceae, Gnaphalieae) consists of about 60 species primarily distributed in tropical and subtropical America. Gamochaeta americana and G. coarctata are closely related species that have been mainly differentiated by its phyllary apices, plant height, width of basal leaves, and involucre height. In order to evaluate whether G. americana and G. coarctata can be differentiated on a morphological basis, we performed a morphometric analysis. A matrix of 24 morphological characters and 99 specimens was analyzed using two multivariate approaches: Cluster Analysis and Principal Coordinate Analysis. Both, the dendrogram and the Principal Coordinate Analysis (PCoA), showed that the two species are not clearly distinguished. No discriminating morphological characters for the two species have been found. In conclusion, all available data support that G. coarctata should be considered a synonym of G. americana. Lectotype is designated for Gnaphalium purpureum var. macrophyllum, and G. americana is described and illustrated.